Effect of thyme essential oil supplementation on feed intake, apparent digestibility, rumen fermentation, blood parameters and in vitro methane yield of Nellore cattle - Castro Filho, Edivilson Silva [UNESP]; Roma Junior, Luiz Carlos; Bertocco Ezequiel, Jane Maria [UNESP]; Vieira Salles, Marcia Saladini; Costa Almeida, Marco Tulio; Perez, Henrique Leal; Suguino, Eduardo; Castello Branco van Cleef, Eric Haydt (Elsevier B.V., 2021)
The objective of this study was to evaluate the effects of thyme essential oil (TEO) supplementation, which has recognized antimicrobial and antioxidant activity, on feed intake, feeding behavior, ruminal fermentation and blood parameters of feedlot Nellore cattle, aiming to indicate the ideal TEO dose. Four ruminally-cannulated Nellore steers (500 +/- 44 kg body weight) were randomly assigned in a 4 x 4 Latin square design and received one of the following experimental treatments: CON = control, with no TEO (423 g thymol/kg DM); T2 = 2 mL/d of TEO; T4 = 4 mL/d of TEO; and T8 = 8 mL/d of TEO. Each experimental period lasted 21 d (14 d for adaptation and 7 d for data collection). Dry matter (DM) intake and digestibility were not affected by TEO infusion (P=0.11). Among feeding behavior variables, only standing still activity differed with TEO inclusion (Linear, P=0.03), with greater values observed when greater TEO doses were used. The in vitro total gas production was quadratically affected by TEO infusion (P=0.05). Ruminal pH tended to increase linearly from CON to T8 (P=0.09), while ammonia nitrogen concentrations tended to be quadratically affected (P=0.09). No TEO effect was observed for short-chain fatty acids (P=0.11). TEO also did not affected blood parameters evaluated in this trial (erythrogram, leucogram, metabolites and liver enzymes [P=0.11]). The TEO infusion of up to 8 mL/d did not promote deleterious effects on in vitro and in vivo nutritional and metabolic parameters of feedlot Nellore cattle. Further studies should be conducted to investigate the ideal TEO dose to improve beef cattle efficiency.
Keywords: Additive; Antimicrobial agent; Phytotherapy; Thyme; Thymol